Personality Dimensions as Common and Broadband-Specific Features for Internalizing and Externalizing Disorders - Hink, Laura K. (2013)
Several researchers have suggested that the nature of the covariation between internalizing and externalizing disorders may be understood better by examining the associations between temperament or personality and these disorders. The present study examined neuroticism as a potential common feature underlying both internalizing and externalizing disorders and novelty seeking as a potential broad-band specific feature influencing externalizing disorders alone. Participants were 12- to 18-year-old twin pairs (635 monozygotic twin pairs and 691 dizygotic twin pairs; 48% male and 52% female) recruited from the Colorado Center for Antisocial Drug Dependence. Genetic and nonshared environmental influences shared in common with neuroticism influenced the covariation among distinct internalizing disorders, the covariation among distinct externalizing disorders, and the covariation between internalizing and externalizing disorders. Genetic influences shared in common with novelty seeking influenced the covariation among externalizing disorders and the covariation between major depressive disorder and externalizing disorders, but not the covariation among internalizing disorders or between anxiety disorders and externalizing disorders. Also, after accounting for genetic and environmental influences shared in common with neuroticism and novelty seeking, there were no significant common genetic or environmental influences among the disorders examined, suggesting that the covariance among the disorders is sufficiently explained by neuroticism and novelty seeking. We conclude that neuroticism is a heritable common feature of both internalizing disorders and externalizing disorders, and that novelty seeking is a heritable broadband specific factor that distinguishes anxiety disorders from externalizing disorders. Keywords: internalizing, externalizing, neuroticism, novelty-seeking, genetics, environment